Profil Pengelolaan Keuangan Badan Usaha Milik Desa di Sumba Timur - Yulita Milla Pakereng; Pingky Alfa Ray Leo Lede (Universitas Pendidikan Indonesia, 2022)
As a profit-oriented entity belonging to a village, the Village-Owned Enterprise (BUMDesa) certainly carries out its business activities to improve the economy in the village. However, many problems, such as the financial management of BUMDes often occur and cause the businesses run by BUMDes to not develop. In East Sumba Regency, East Nusa Tenggara Province, 66.43 percent of BUMDes are inactive and stagnant. This was explained by the East Sumba Regency Community and Village Empowerment Service as a problem of unprofessional financial management. With a sample of 14 BUMDes, this study provides an overview or description related to financial management. The results show that from 2018 to 2019 financial management is getting better, but it is necessary to improve business financial management in the future.